Analisis Pelanggaran Pemakaian Tenaga Listrik Pada Pelanggan di PT. PLN (PERSERO) ULP Bumiayu Di Masa Pandemi Covid-19 - Dian Ayu Kusuma Intan; Rizki Noor Prasetyono (Journal of Electronic and Electrical Power Applications, 2021)
Electric energy is a very important energy because it is used by good people for housing, offices, business, and industry. As many as 75.7 million PLN customers in Indonesia with the use of electrical equipment, and the development of the modern era, especially in the covid-19 pandemic as it is today, led to the emergence of violations aimed at circumventing the use of electricity so that the bills do not soar. To solve this problem, PLN has P2TL (Electricity Usage Control) activities aimed at suppressing non-technical shrinkage and avoiding customer fraud. The result of this study is that it can classify the type of violations on electricity users during the Covid-19 Pandemic precisely in August 2020, calculated as many as 93 Electricity Customers in PT. PLN (Persero) ULP Bumiayu, with Violations of Class I / K2 as many as 89 Customers, Violations of Class II as much as 1 Customer, and Violations of Class IV as many as III Customers. Violators of electricity users are sanctioned in the form of follow-up bills that are adjusted based on the type of group.